Practices of 21st Century Skills by School Leaders in Rawalpindi City: Mehr Bakht, Salma Nazar Khan - Mehr Bakht,; Salma Nazar Khan, (JELM, 2023)
21st century is different than 20th in citizenship and abilities, thus requires a different set of skills expected differently in each field (Dede, 2009). This study intended to explore the practices of school leaders of Rawalpindi city secondary schools about 21st century 4 Cs leadership skills; Competence, Character, Compassion & Courage. This was an exploratory research. Survey method quantitative research approach was used. An adapted questionnaire was used to collect the quantitative data. All the school leaders of Rawalpindi city were the population of the study. Through simple random sampling 98 school leaders were selected to answer questionnaire. The finding of the study indicates that 4Cs leadership skills are practiced by School leaders in their school. School leaders use motivation (mean= 4.251), accountability (mean= 4.13), problem solving (mean= 4.12), and social leadership (mean= 4.13) skills most than other sub-skills in their practices. School leaders found themselves more social and accountable towards society. This study is significant for school leaders as they will find out the importance of 21st century leadership skills in their leadership positions. The finding of the study recommends that there should be training and workshop for school leaders about 21st century leadership skills.